THE IMPACT OF COLLABORATIVE STRATEGIC READING (CSR) STRATEGY ON READING SKILL AMONG SECONDARY STUDENTS - Riswanto Riswanto (University of Kuningan, 2023)
The study's overarching objective is to determine whether or not CSR improves students' reading comprehension. Twenty-five students from one public secondary school in Bengkulu Tengah served as the study's sample. The study used a pre- and post-test to gather data in a quasi-experimental equivalent time-series design. Since there is only one group in the research, a control group is unnecessary. The normality of the data was a prerequisite for using the one sample t-test formula to assess the hypothesis. In this study, the researchers employed the Kolmogorov-Smirnov test to examine whether or not the data were normally distributed. The results of this research showed that the experimental group's class post-test mean score of 83.54 exceeded the class pre-test mean score of 51.94. Based on the findings, it is clear that the Collaborative Strategic Reading (CSR) approach significantly improved students' ability to understand what they read.